Re-Thinking Loft Buildings in the Scope of Housing Production in Turkey - Hizli, Neslinur; Mizrak, Burcin (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
In an age of rapid urbanization, the question of how housing should respond to increasing, changing demands of cities has become crucial. The aim of the present study was to re-envision the role of the loft building in housing production in Turkey in terms of responding to those needs, and to discuss loft buildings within the context of an open building-embodying adaptability, variability, and flexibility. To do so, literature was reviewed, and six examples, three national and three international, were analyzed. Two interviews were conducted, one with a member of a design team, and one with a user of loft examples. The study demonstrates that loft buildings embody the fundamentals of the open building concept, with high ceilings and structural systems that provide interior space without division, but which diverge from the concept due to restrictions in their facades. It also suggests that lofts can play a remarkable role in future Turkish housing production due to these open building characteristics.
Keywords: Loft buildings; open building; support and infill; user participation; the SAR system; Architecture